Cechy gatunkowe morning show na przykładzie audycji Wstawaj, szkoda dnia w radiu RMF FM - Garcarek-Sikorska, Agnieszka (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
The morning show is a new journalistic genre found in commercial broadcasting. This type of morning show consists of a few hours of block programming. A morning show consists of popular music, game shows, aspects of a talk show, call-in jokes, and news reports, but the most important feature is the personality DJs. This article is an attempt at characterizing this genre.